Development of Epoxy Based Surface Tolerant Coating Improvised with Zn Dust and MIO on Steel Surfaces. (3rd April 2014) - Jain, Rachna; Wasnik, Manish; Sharma, Amit; Kr Bhadu, Manish; Rout, T. K.; Khanna, A. S.
Abstract : Couple of high strength and flexible surface tolerant coatings were designed for oil contaminated, rusty, and minimally prepared steel surfaces. These coatings are to have strong interfacial adhesion due to low surface tension and sustain more than 5 MPa pull out force consistently. The effect of optimized concentration of zinc dust and micaceous iron oxide (MIO) as pigments is evaluated for these surface tolerant coating systems. It has been noticed that the presence of these two ingredients has enhanced corrosion resistance more than several times as compared to commercially available coating systems. The corrosion simulation test in 3.5 wt.% NaCl has evident for significant improvement in terms of delaying blistering and delamination. The high pore resistance (R p ) indicates the slow migration of ions and water into the substrate and coating interface, which could be the reason of the improvement in corrosion process.